A Randomized, Open-Label Study of the Safety and Efficacy of Switching Stavudine or Zidovudine to Tenofovir Disoproxil Fumarate in HIV-1–infected Children With Virologic Suppression. Issue 4 (April 2015) - Saez-Llorens, Xavier; Castaño, Elizabeth; Rathore, Mobeen; Church, Joseph; Deville, Jaime; Gaur, Aditya; Estripeaut, Dora; White, Kirsten; Arterburn, Sarah; Enejosa, Jeffrey V.; Cheng, Andrew K.; Chuck, Steven L.; et al.
Abstract : Background: The safety and efficacy of tenofovir disoproxil fumarate (TDF) in HIV-1–infected children have not been evaluated in a randomized controlled trial. Methods: Subjects (2 to <16 years) on a stavudine (d4T) or zidovudine (ZDV) containing regimen with HIV-1 RNA <400 copies/mL were randomized to either switch d4T or ZDV to TDF or continue d4T or ZDV. The primary endpoint was the proportion of subjects with HIV-1 RNA < 400 copies/mL at Week 48 with a prespecified noninferiority margin of 15%. After the 48-week randomized phase, eligible subjects were rolled over to an extension phase. Results: Ninety-seven children (48 TDF vs. 49 d4T or ZDV) were randomized and treated. The percent of subjects who maintained virologic suppression in the TDF versus d4T or ZDV group at Week 24 were 93.8% versus 89.8% (difference 4.0%; 95% confidence interval:: −6.9% to 14.9%) and at Week 48 were 83.3% versus 91.8% (difference: −8.5%; 95% confidence interval: −21.5% to 4.5%; missing = failure, intent-to-treat analysis). No subjects discontinued study drug because of an adverse event in the 48 weeks of randomized phase. Four subjects discontinued TDF because of proximal renal tubulopathy in the extension phase. Conclusions: Our study did not demonstrate noninferiority of TDF versus d4T or ZDV at Week 48. Overall safety and tolerability of TDF in children were consistent with adults. TDF may be considered as an alternative to d4T or ZDV in HIV-infected children. Abstract : Supplemental Digital Content is available in the text.